Buparvaquone is active against Neospora caninum in vitro and in experimentally infected mice. Issue 1 (April 2015) - Müller, Joachim; Aguado-Martinez, Adriana; Manser, Vera; Balmer, Vreni; Winzer, Pablo; Ritler, Dominic; Hostettler, Isabel; Arranz-Solís, David; Ortega-Mora, Luis; Hemphill, Andrew
Highlights: Buparvaquone inhibits proliferation of Neospora caninum at nanomolar concentrations. In vitro, the drug acts mainly parasitostatic. Parasiticidal effects occur at µmolar concentrations after extended periods of time. Buparvaquone acts slowly as evidenced by transmission electron microscopy. Buparvaquone prevents clinical signs of acute neosporosis in mice. Graphical Abstract: Abstract: The naphthoquinone buparvaquone is currently the only drug used against theileriosis. Here, the effects of buparvaquone were investigated in vitro and in an experimental mouse model for Neospora caninum infection. In 4-day proliferation assays, buparvaquone efficiently inhibited N. caninum tachyzoite replication (IC50  = 4.9 nM; IC100  = 100 nM). However, in the long term tachyzoites adapted and resumed proliferation in the presence of 100 nM buparvaquone after 20 days of cultivation. Parasiticidal activity was noted after 9 days of culture in 0.5 µM or 6 days in 1 µM buparvaquone. TEM of N. caninum infected fibroblasts treated with 1 µM buparvaquone showed that the drug acted rather slowly, and ultrastructural changes were evident only after 3–5 days of treatment, including severe alterations in the parasite cytoplasm, changes in the composition of the parasitophorous vacuole matrix and a diminished integrity of the vacuole membrane. Treatment of N. caninum infected mice with buparvaquone (100 mg/kg) either by intraperitoneal injection or gavage prevented neosporosis symptoms in 4 out of 6 mice in the intraperitoneally treated group, and in 6 out of 7 mice in the group receiving oral treatment. In the corresponding controls, all 6 mice injected intraperitoneally with corn oil alone died of acute neosporosis, and 4 out of 6 mice died in the orally treated control group. Assessment of infection intensities in the treatment groups showed that, compared to the drug treated groups, the controls showed a significantly higher parasite load in the lungs while cerebral parasite load was higher in the buparvaquone-treated groups. Thus, although buparvaquone did not eliminate the parasites infecting the CNS, the drug represents an interesting lead with the potential to eliminate, or at least diminish, fetal infection during pregnancy.